Excavations at the Seila Pyramid and Fag El-Gamous Cemetery - Pierce, Krystal V. L.,; Jensen, Bethany,; Muhlestein, Kerry, (Medieval Law and Its Practice;, 2020)
In Excavations at the Seila Pyramid and Fag el-Gamous Cemetery, the excavation team provides crucial information about the Old Kingdom and Graeco-Roman Egypt. While both periods have been heavily studied, Kerry Muhlestein and his contributors provide new archaeological information that will help shape thinking about these eras. The construction and ritual features of the early Fourth Dynasty Seila Pyramid represents innovations that would influence royal funerary cult for hundreds of years. Similarly, as one of the largest excavated cemeteries of Egypt, Fag el-Gamous helps paint a picture of multi-cultural life in the Fayoum of Egypt during the Ptolemaic and Roman periods. Excavations there provide a statistically impactful understanding of funerary customs under the influence of new cultures and religion.